Strong motion earthquake data values of digitized strong-motion accelerograms, 1933-1994 - National Geophysical Data Center / World Data Service (NGDC/WDS) (PANGAEA, 2025)
The Strong Motion Earthquake Data Values of Digitized Strong-Motion Accelerograms is a database of over 15,000 digitized and processed accelerograph records from 1933 to 1994. Data were obtained from a variety of structural and geologic environments. Most of the data are available in three levels of processed files. The first type of file contains raw (uncorrected) time, history data points digitized from the analog accelerogram. The second is a filtered, instrument corrected version of the time, history data. This file also contains calculated velocities and displacements obtained by the integration and double integration of the corrected accelerations. The third type of file includes the calculated Fourier and response spectra data. The data are from the United States, Algeria, Argentina, Armenia, Australia, Bulgaria, Canada, Chile, China, El Salvador, Fiji, Germany, Greece, India, Iran, Italy, Japan, Mexico, New Zealand, Nicaragua, Papua New Guinea, Peru, Portugal, Romania, Spain, Taiwan, Turkey, and Uzbekistan. This database is static and is no longer being updated. This dataset has been archived in the framework of the PANGAEA US data rescue initiative 2025.